Analisis Aliran Air Tanah Menggunakan Alat Ukur Paper Disc Velocimeter (PDV) Di Lahan Gambut - Reski Daini Ramawilis; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Peat restoration on peatlands is needed to restrain the rate of further damage from peatland ecosystems, one of which is a peat rewetting activity that is a way to re-wet the peatland using canal blocking to keepthe groundwater level at max 0.4 meters below the surface. Groundwater flow analysis was carried out in Lukun Village, Tebing Tinggi Timur District, Meranti Islands using Paper disc velocimeter (PDV)and groundwater level measurements using measuring pipes on 5 deep wells on the upstream transect and 5 deep wells on the downstream transect with a distance of 50 m and 100 m canal blocking. Theresults obtained from the Velocimeter Paper disc are the velocity and direction of flow in the upstream and downstream transects of the canal blocking, where groundwater flow rates are higher in thedownstream and lower in the upstream due to canal blocking. The benefit of having a canal block is that the groundwater flow rate in the upstream transect can be held up to the canal because the elevation ofthe channel's water level has been successfully raised.Keywords : peatland, canal blocking, paper disc velocimeter, groundwater flow.